Wilhelmina Barns-Graham - The glaciers - Carr, Holly Corfield 1987-; Cousins, Mark; Hallett, Alyson; Heydon, Tilly; Nienow, Peter; Pennington, Cassia; Strang, Alice 1973- (Lund Humphries, 2024)
"In May 1949, the Scottish artist Wilhelmina Barns-Graham (1912-2004) visited the Grindelwald Glacier in Switzerland. It was a trip which would have a profound and lasting impact on her work. Charting the journey, the beautiful work it stimulated and wider questions around glacial landscapes, then and now, this publication provides insights that will expand our understanding of both an acclaimed body of work and the artist who created it. That Barns-Graham produced her final glacier painting in 1994, some 45 years after her sole visit to Switzerland, is testament to the influence that the experience had on her. So too are her 100 or so individual glacier works - made first between 1949 and 1952 and then in revisiting the subject between 1976 and 1994. Including a complete catalogue of the glacier paintings, this book presents the definitive account of a trip that would transform the artistic imagination of one of the foremost British painters of the twentieth century."
Keywords: Barns-Graham, Wilhelmina -- 1912-2004; Bildband